Cluster Computing: Emerging Technologies, Benefits, Architecture, Tools and Applications - Ranjit Rajak (International Journal of Advanced Science and Technology, 2020)
The Computing paradigm is changing from sequential to parallel, now cluster computing. Whole world in technology direction is working towards to find the efficient and cost effective computing environment. Cluster computing is among them which is using almost every area of research where processing of huge data demands. Cluster computing is faster in speed, effective in result and low cost. These three attributes make it popular. This paper starts from brief introduction of cluster with a block diagram and various classification of cluster depends on some factors. Also, the study of various challenges, benefits, applications and drawbacks of the cluster computing. It discussed different tools and projects which are used in cluster computing. The entire aspects of cluster computing paradigm helps to understand and easy to decide their real world applications and gives some generic ideas in the world of computing technology. This can be easy to understand and differentiate with other computing models such as cloud and grid computing.